Urbanization and aging in ASEAN: a comparative demographic analysis from 1970 to 2023 - Asykal Syakinah Mohd Ali,; Syahrul Nizam Junaini,; Tarmiji Masron,; Kimura, Yoshinari; Azizul Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Urbanization is a major driver of global demographic shifts, particularly affecting Southeast Asian aging trends. This study investigates the relationship between urbanization and the aging population across ASEAN countries and selected other nations, focusing on data from 1970 to 2023. Using cross-sectional comparative analysis and multiple linear regression, the study examines key demographic indicators, including urbanization rates, elderly population proportions, fertility rates, and life expectancy. Addressing a notable research gap in the ASEAN context, the findings reveal a strong positive association between increased urbanization and aging demographics, particularly in rapidly developing countries like Singapore and Thailand. Conversely, countries with lower urbanization rates exhibit slower aging trends. The results underscore how urbanization, fertility decline, and healthcare improvements interact to shape of demographic aging. The study concludes that ASEAN countries are undergoing a dynamic demographic transition, with implications for urban planning, healthcare policy, and social support systems. These insights contribute to understanding the complex interplay between urban development and aging and emphasize the urgency for region-specific policy interventions to manage future demographic challenges.